Seismic Wave Stencil Computation Performance Comparison - Freitas, Ágatha de; Cilento, Lucas; Guimarães, Renato S.; Souza, Jaime F.; Senger, Hermes; Gomi, Edson S. (Anais da Escola Regional de Alto Desempenho de São Paulo (ERAD-SP); 2022: Anais da XIII Escola Regional de Alto Desempenho de São PauloDO - 10.5753/eradsp.2022.222249, 2022)
This work aims to provide comparative results between OpenCL and oneAPI performance on FPGAs, GPUs and CPUs regarding the execution of stencils in the simulation of seismic acoustic wave propagation. Our results show that the naive stencil code performs better on GPU and CPU than FPGA without strong knowledge on how to implement optimizations. Another result is that oneAPI code is easier and faster to implement than OpenCL as it automatically applies some FPGA-specific optimizations at compile time.